On the importance of Synantropic animals in the control of Chagas' disease (endemic) - Rocha e Silva, Eduardo Olavo da; Andrade, José Carlos Rehder de; Lima, Anísio Ribeiro de (Revista de Saúde Pública, 1975)
Emphasis is layed upon the fact that in some areas, the routine methods used to control vectors of Chagas' disease, must be complemented by seizure activities of T. cruzi reservoirs, specially marsupials (Didelphis) and rodents (Rattus). A study was undertaken in some municipal districts of the Administrative Region of Campinas, State of S. Paulo, where the presence of reservoirs and peridomestic triatomines (Panstrongylus megistus) allow favourable conditions for the reintroduction of the domiciliary parasitic cycle. The results of the search of Trypanosoma type cruzi in these triatomines and the mentioned reservoirs are commented. Their association with the precipitin reaction in order to allow detection of the type of blood ingested by the P. megistus captured in the houses was studied.